Family case of aromatic L-amino acid decarboxylase deficiency - O. B. Kondakova; K. A. Kazakova; A. A. Lyalina; N. V. Lapshina; A. A. Pushkov; N. N. Mazanova; Yu. I. Davydova; D. I. Grebenkin; I. V. Kanivets; K. V. Savostyanov (Нервно-мышечные болезни)
Aromatic L‑amino acid decarboxylase (AADC) deficiency is rare autosomal recessive neurometabolic disorder. It caused by generalized combined deficiency of serotonin, dopamine, norepinephrine and adrenaline. This disorder is characterized by muscular hypotonia, motor development delay, oculogyric crises and impairment of the autonomic nervous system.Laboratory diagnostic of AADC deficiency in Russian Federation includes determination of the concentration of 3‑O‑methyldophamine in dried blood spots by tandem mass spectrometry and molecular analysis of the DDC gene by Sanger sequencing or next generation sequencing.Therapy of AADC deficiency includes combination of drugs which increase the formation of dopamine, inhibit its reuptake and increase the residual activity of the enzyme. The first‑line drugs are selective dopamine agonists, monoamine oxidase inhibitors of type B and vitamin B6 supplements.We present the case of management and treatment of patients with AADC deficiency. The patient’s condition was improved by using of combination therapy with pyridoxal‑5‑phosphate, pramipexole and selegiline. Significant positive dynamics was achieved on pyridoxal‑5‑phosphate therapy for the first time.